PRODUCTION AND UTILIZATION OF RUBBER WOOD IN THAILAND: I. PLANTATION AREAS AND WOOD PRODUCTION - Urapeepatanapong, Chavalit (วารสารวนศาสตร์ไทย, 2022)
Rubber tree has been introduced from Malaysia to southern Thailand since 1899.Total areas planted up to 1986 were of 1, 717, 561 ha, 10.08% in the East and 89.94% in the South. The Office of Rubber Replanting Aid Fund found in 1961 already replanted the low3-yield-original varieties from 1961 to 1987 of 647, 809 ha. The areas of 677, 789 ha are expected to be replanted in future with the replanting target of 50,000 ha/year. Based on the standard spacing of 3x8 m, rubber wood gained from the 19, 20, 21, 22, 23, and 24-year-old plantations were of 145.69, 161.26, 167.94, 170.50, 176.88, and 207.75 m3/ha with an average of 171.67 m3/ha. This output consisted of 49.05% roundwood or sawn timber, 38.72% fuelwood or wood residues, and 12.23% pole and pile. It is expected that rubber wood harvested from the future replanting program should be about 8,584,735 m3/year divided into 3,272,364 m3 wood residues, 1,049,869 m3/ pole and pile. and 4,262,142 m3 roundwood.